Price on Expressionism and the Placement Problems - Kalpokas, Daniel (Análisis. Revista de investigación filosófica, 2014)
Resumen En “Naturalismo sin representacionalismo”, Huw Price propone una variedad de naturalismo –una que él denomina naturalismo del sujeto– que supuestamente puede evitar los problemas de la localización relacionados con entidades “incómodas” como son los hechos morales, los significados, las verdades matemáticas y otras similares. A partir de una concepción expresivista de todo el lenguaje, Price defiende que los problemas de la localización descansan sobre un error categorical: el error consiste en considerar que toda oración representa algún estado de hechos mundano. En nuestro trabajo, a partir de nuestra crítica al expresivismo de Price, cuestionaremos su respuesta a los problemas de la localización. Palabras clave: Naturalismo del sujeto, representacionalismo, expresivismo global, deflacionismo, verdad. Abstract In his article “Naturalism Without Representationalism”, Price proposes a variety of naturalism –subject naturalism, as he calls it- that is supposedly able to avoid placement problems about “odd” entities such as moral facts, meanings, mathematical truths and the like. Assuming an expressivist conception about the entire language, Price argues that placement problems rest on a category mistake: the mistake of considering all sorts of sentences as representing worldly states of affairs. In this article, by arguing against Price’s expressivism, I call his response to placement problems into question. My thesis is that placement problems are genuine ontological problems. Key Words: Subject Naturalism, Representationalism, Global Expressivism; Deflationalism; Truth.